Analysis Amr in the Book of Ṣuwar min Ḥayātiṣ-Ṣahābah by Dr. Abdurrahman Ra’fat Al-Basya (Al-Ma’ānī Study) - Nurhaliza, Siti; Komarudin, Edi; Mardiansyah, Yadi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to analyze the form and meaning of amr as well as the structural components of imperative sentences in the book Ṣuwar min Ḥayātiṣ-Ṣaḥābah by Dr. Abdurrahman Ra’fat Al-Basha, using a semantic approach. This approach focuses on the meaning of language within a specific context. A semantic approach allows for an analysis of how the meaning of amr can vary depending on its situational usage, whether literal (Ḥaqīqī) or figurative (majāzī). The research method employed is descriptive-analytic, which serves to describe and provide an overview of the object under study through collected data or samples. The data were obtained from excerpts containing imperative verbs (fiʻl amr), which were classified according to their form and implied meaning, and then analyzed based on the theory of amr proposed by Ahmad Al-Hāsyimī. The results of this study indicate that the concept of amr in Ṣuwar min Ḥayātiṣ-Ṣaḥābah encompasses seven meanings: 55 instances of literal command (Ḥaqīqī), 2 of honoring (ikrām), 4 of permission (iʾzn), 28 of supplication (duʿāʾ), 43 of guidance (irshād), 17 of request among equals (iltimās), and 8 of threat (tahdīd). Morphologically, the imperative forms appear in two patterns: fiʻl mujarrad (basic/root verbs) and fiʻl mazīd (augmented verbs), both transitive and intransitive. Syntactically, the structure of amr typically follows the pattern: verb (fiʻl) – subject (fāʻil) – object (mafʻūl bih) – preposition (ḥarf jar) and vocative (nida'). Keywords: Balaghah, Fi'il Amr, Ṣuwar min Ḥayātiṣ - Ṣahābah